2020
DOI: 10.3390/ijms21134757
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ER Stress in Acute Lymphoblastic Leukemia Cells by the Deubiquitinase Inhibitor VLX1570

Abstract: The proteasome is a validated target of cancer therapeutics. Inhibition of proteasome activity results in the activation of the unfolded protein response (UPR) characterized by phosphorylation of eukaryotic initiation factor 2α (eIF2α), global translational arrest, and increased expression of the proapoptotic CHOP (C/EBP homologous protein) protein. Defects in the UPR response has been reported to result in altered sensitivity of tumor cells to proteasome inhibitors. Here, we characterized the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
4
18
0
Order By: Relevance
“…We found that HMOX1 was induced in MOLM-14 cells at 32 nM VLX1570 and at 64 nM VLX1570 in KG1a cells ( Figure 4 ). HMOX1 was not, however, induced at high concentrations of VLX1570, consistent with previous observations of inhibition of elongation of translation at high concentrations of this compound [ 39 ]. We conclude that the Nrf2 target HMOX1 is induced at lower concentrations of VLX1570 in the more sensitive MOLM-14 cell line.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that HMOX1 was induced in MOLM-14 cells at 32 nM VLX1570 and at 64 nM VLX1570 in KG1a cells ( Figure 4 ). HMOX1 was not, however, induced at high concentrations of VLX1570, consistent with previous observations of inhibition of elongation of translation at high concentrations of this compound [ 39 ]. We conclude that the Nrf2 target HMOX1 is induced at lower concentrations of VLX1570 in the more sensitive MOLM-14 cell line.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with a recent report [ 16 ], we found that VLX1570 induces the accumulation of polyubiquitinated proteins and of Hsp70 in AML cells at the concentration range where the loss of cell viability is observed. Similar results have been reported using other types of tumor cells [ 39 , 48 ]. We also found a dose- and time-dependent induction of the ER chaperone Grp78/BiP in MOLM-14 and KG1a AML cells, indicating the induction of ER stress.…”
Section: Discussionsupporting
confidence: 90%
“…VLX1570 was indeed shown to inhibit translation by another mechanism, at the level of translational elongation, in a recent study. 114 …”
Section: Targets Described For Dienone Compoundsmentioning
confidence: 99%
“… 17 , 18 The antiproliferative effect of these agents has been reported on several solid tumors 19 , 20 and lymphoid malignancies. 21 , 22 , 23 , 24 , 25 These agents lead to a similar pattern to the expression of genes induced by 20S proteasome inhibitors 26 and show high susceptibility to bortezomib‐resistant cells. 27 , 28 …”
Section: Introductionmentioning
confidence: 97%
“…Novel proteasome DUBs inhibitors, b‐AP15 and VLX1570 (a derivative of b‐AP15), predominantly target ubiquitin‐specific protease 14 (USP14) and interfere with the proteasomal degradation by inhibiting the activities of the proteasome DUBs, such as USP14 and ubiquitin C‐terminal hydrolase L5 (UCHL5) localized on the 19S proteasome 17,18 . The antiproliferative effect of these agents has been reported on several solid tumors 19,20 and lymphoid malignancies 21‐25 . These agents lead to a similar pattern to the expression of genes induced by 20S proteasome inhibitors 26 and show high susceptibility to bortezomib‐resistant cells 27,28 …”
Section: Introductionmentioning
confidence: 99%